The Role of the Pictoword Game in Boosting Students' Vocabulary Achievement at Mts Negeri 1 Sragen - warsono, warsono; Sujito, Sujito (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study aims to demonstrate the effectiveness of implementing the pictoword game on students' vocabulary achievement in seventh graders at MTs Negeri 1 Sragen. The author used a quantitative research method with a quasi-experimental design. The author took student samples through purposive sampling. The pre-test results showed that the experimental group scored lower than the control group. The average pre-test score in the experimental group was 61.36 and the average pre-test of the control group was 65.60. The two groups were given pre-tests at the same time. The experimental group received four sessions of treatment while learning vocabulary using the Pictoword game. The control group learned vocabulary only through conventional learning. To determine whether the experimental group improved their vocabulary achievement, the authors conducted a post-test. The authors used the IBM SPSS Statistics Base 22.0 program to calculate all data in this study. The results of this study showed that the experimental group's average score increased to 86.33, while the control group's average post-test score was 84.77. Only the experimental group improved their vocabulary achievement because they were treated with four tests using the Pictoword Game. Hypothesis analysis also determined that the alternative hypothesis (Ha) was accepted, meaning there was a significant effect in implementing the pictoword game on students' vocabulary achievement. This study can be concluded that using the pictoword game can help students learn vocabulary more easily but in a fun way, stimulate students to learn more actively, and also improve students' vocabulary achievement.